Fabrication and characterization of ZrO2 nanofibers by critical bubble electrospinning for high-temperature-resistant adsorption and separation. Issue 5 (July 2019) - Li, Ya; He, Ji-Huan
In this study, a novel and simple approach to fabricate zirconium dioxide (ZrO2 ) nanofibers by critical bubble electrospinning and subsequent thermal treatment was reported. The influences of different matrixes, weight percentages, heating rates, post-processing techniques, and with/without carbonization were discussed. The fiber size grew linearly with the increasing amounts of particles added. In addition, ZrOCl2 /PAN composite fibers were converted to ZrO2 nanofibers after high-temperature calcination, whose crystal structure was cubic phase of ZrO2 after 1000°C, and the obtained ZrO2 nanofibers shows excellent high-temperature-resistant adsorption and separation properties.